Expression of Indoleamine 2,3-Dioxygenase Induced by IFN-γ and TNF-α as Potential Biomarker of Prostate Cancer Progression - Banzola, Irina; Mengus, Chantal; Wyler, Stephen; Hudolin, Tvrko; Manzella, Gabriele; Chiarugi, Alberto; Boldorini, Renzo; Sais, Giovanni; Schmidli, Tobias S.; Chiffi, Gabriele; Bachmann, Alexander; Sulser, Tullio; et al. (Frontiers in Immunology, 2018)
Inflammation has been suggested to play an important role in onset and progression of prostate cancer (PCa). Histological analysis of prostatectomy specimens has revealed focal inflammation in early stage lesions of this malignancy. We addressed the role of inflammatory stimuli in the release of PCa-specific, tumor-derived soluble factors (PCa-TDSFs) already reported to be mediators of PCa morbidity, such as 2, 3-indoleamine dioxygenase (IDO) and interleukin (IL)-6. Inflammation-driven production and functions of PCa-TDFSs were tested “in vitro” by stimulating established cell lines (CA-HPV-10 and PC3) with IFN-γ or TNF-α. Expression of genes encoding IDO, IL-6, IFN-γ, TNF-α and their receptors was investigated in tumor tissues of PCa patients undergoing radical prostatectomy (RP), in comparison with benign prostatic hyperplasia (BPH) specimens. In established cell lines, IFN-γ and TNF-α-treatment resulted in the induction of IDO and IL-6 gene expression and release, respectively, suggesting that induction of PCa-TDSFs by these cytokines might contribute to progression of cancer into an untreatable phenotype. An analysis based on timing of biochemical recurrence (BR) revealed the prognostic value of IDO but not IL-6 gene expression in predicting recurrence-free survival (RFS) in patients with PCa. In addition, a urine-based mRNA biomarker study revealed the diagnostic potential of IDO gene expression in urines of men at risk of PCa development.